Educational Organizations as Loosely Coupled Systems - Weick, Karl E. (Administrative Science Quarterly, 1976)
Abstract The image Karl Weick (born 1936, meanwhile retired professor of psychology and organizational behavior at Cornell University, Ithaca, NY) uses as an introduction for his “classic” essay on loosely coupled systems is at the same time bizarre and fascinating. Had the economic discussion on supply chain management and value creation systems already taken place in the 1970s, maybe he would have transferred his unconventional football metaphor to the “logistics playing field” of modern supply networks.